Frontiers of Sound in Design A Guide for the Development of Product Identity Through Sounds - Dal Palù, Doriana (SpringerBriefs in Applied Sciences and Technology,, 2018)
This book serves as a guide to developing and designing the right sound to enhance a product's identity, its use, its affordance and its acceptance by consumers. It is of interest to designers, researchers, R&D departments, marketing experts and industries involved in the exploration of the new frontiers now offered by sound. We are all immersed in an intangible world of sounds; however, the fact that only an infinitesimal part of the sound to which we are exposed has been wittingly created is often ignored. An interdisciplinary and trans-disciplinary approach encompassing design methods and design engineering, psychology and cognitive ergonomics, acoustics and psychoacoustics contributes to the improvement of product sound development. Providing readers with an overview of design methods in which sound becomes a new requirement, the book investigates the role of sound from the consumer viewpoint, presents several tools and practical examples of sensory design tools and projects, and lastly, introduces a new tool and method developed expressly to support the design of product sound.